Effects of cavitation in common-rail diesel nozzles on the mixing process - López, J. Javier; De la Garza, Oscar A.; De la Morena, Joaquín; Martínez Martínez, Sergio (Professional Engineering Publishing, 2017)
Abstract A study to experimentally analyze the effect of cavitation on the mixing process in diesel nozzles was carried out. The mixing process was studied through the spray cone angle. It was characterized in two different scenarios: with the liquid length (nearly realistic conditions, that is, evaporative but non-reactive spray) and the heat release fraction (fully realistic conditions, that is, evaporative and reactive spray). In both studied scenarios, the increase in spray cone angle caused by the cavitation phenomenon, which leads to a better mixing process, has been confirmed. Nevertheless, when the variations of the effective injection velocity and the spray cone angle obtained by comparing a cylindrical nozzle (i.e. a nozzle that promotes the cavitation phenomenon) with a conical nozzle (i.e. a nozzle that inhibits this phenomenon) were analyzed together, it was found that, for the cases studied here, the mixing process worsens with the cylindrical nozzle. Keywords Diesel nozzle, cavitation, injection process, spray cone angle, combustion process